EXPLORING OF CONSUMER BEHAVIOR TOWARDS FAST-FOOD INDUSTRY: A CASE STUDY ON PUNE - Patil, Abhijeet L.; Pachpande, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Fast food restaurants have seen a plethora of changes in the long run, since 1921 when White Castle, the first fast food hamburger chain, had sold burgers for five cents piece and ended its first day with a US3.75profit. Fast food refers to the kind of food which can be quickly made and can be served in no time and is commonly known as quick service restaurant (QSR).Fast food is usually one of the most preferred service these days because of the convenience attached to it. The changing life style and increased disposable incomes had lead to a tremendous growth of the fast-food industry. One of the biggest merits of the fast food is that it saves a lot of time thereby enabling the customer to get into multitasking. These days the QSR’s are trying to jump on the bandwagon of the Society’s push to lead a healthier life. More of such strategies are used to highlight on the low-fat and Oil free foods. As per report of Indian Fast food Market Analysis, India is seen as one of the fastest growing fast food markets in the world. The Indian fast food market is growing at an annual growth rate of 30-35%. Some of the popular food chains have huge plans of expansion in future. Domino’s planto open 60-65 outlets every year for the next three years, while Yum Brands Inc is also geared up for its massive expansion plans across the the country.